The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1016/j.ultsonch.2020.105459
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ultrasonic standing waves on flotation bubbles

Abstract: Highlights The dynamic process of bubble and bubble-coal aggregation were visualized. Bubble distributions in ultrasonic fields were studied by image processing. Entrapment and entrainment led to a slight increase of clean coal ash. The highest clean coal yield and combustible recovery obtained at 100 kHz.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 51 publications
0
11
0
1
Order By: Relevance
“…Despite these differences in acoustic impedance and velocity, it was deemed that stainless-steel coupons would still provide valuable insight into the potential application of MBs proximal to highly acoustically reflective surfaces. In particular, it is anticipated that the more reflective steel coupon would favour the onset of a stronger ultrasonic standing wave field, and that the resulting acoustic radiation forces may potentially drive microbubbles away from the target surface and also cause microbubbles to aggregate (Lazarus et al 2017;Jin et al 2021). Differences in substrate properties may also have an impact on the amplitude of MB oscillation during cavitation and affect the probability and direction of resulting microjetting or microstreaming events.…”
Section: Acoustic Properties Of Substrates Used For Biofilm Growthmentioning
confidence: 99%
“…Despite these differences in acoustic impedance and velocity, it was deemed that stainless-steel coupons would still provide valuable insight into the potential application of MBs proximal to highly acoustically reflective surfaces. In particular, it is anticipated that the more reflective steel coupon would favour the onset of a stronger ultrasonic standing wave field, and that the resulting acoustic radiation forces may potentially drive microbubbles away from the target surface and also cause microbubbles to aggregate (Lazarus et al 2017;Jin et al 2021). Differences in substrate properties may also have an impact on the amplitude of MB oscillation during cavitation and affect the probability and direction of resulting microjetting or microstreaming events.…”
Section: Acoustic Properties Of Substrates Used For Biofilm Growthmentioning
confidence: 99%
“…Several investigations indicated that the acoustic force in the ultrasonic standing wave (USW) field might potentially be an attractive force to improve the attractive mineralization process [10] , [11] , [12] . The sound pressure gradient in the USW field and the acoustic force are stronger than other sound field forms [13] .…”
Section: Introductionmentioning
confidence: 99%
“…USW has been widely used in particle separation, emulsion demulsification, crude oil dehydration, and desalination [16] , [17] . In recent years, more attention has been paid to USW-assisted flotation [10] . A successful and efficient mineralization process for fine coal flotation was proposed in the presence of USW field attraction [18] .…”
Section: Introductionmentioning
confidence: 99%
“… 24 Jin et al explored the effect of standing wave ultrasound on flotation efficiency using a high-speed camera technique and discovered that the ultrasonic frequency had a significant effect on bubble aggregation and the number of small bubbles under the Bjerknes force. 25 …”
Section: Introductionmentioning
confidence: 99%
“…24 frequency had a significant effect on bubble aggregation and the number of small bubbles under the Bjerknes force. 25 Recently, the cleaning effect of ultrasound on particle surfaces has been experimentally verified. 26,27 Hong et al revealed that ultrasonic treatment significantly affects the contact angle of the graphite surface.…”
Section: Introductionmentioning
confidence: 99%